The myth of the "out of character" crime - Samenow, Stanton E. (Praeger, 2007)
The "out of character" crime -- Thinking errors as a key to character -- Realities about the "out of character" crime -- Secret controllers -- Sociological and psychological determinism: road to a deadend -- Interviewing the defendant: the setting -- Homicide of a husband by his wife or alter ego? -- The defendant's view of himself or herself as a good person -- Pretensions -- The self as unique and irresistible -- "I think; therefore it is" -- The unimportance of feelings -- The defendant's use of language -- Having a thin skin: susceptibility to putdowns -- The self as the center of the universe -- Six tactics used by defendants to control interviews -- Secret controllers: several cases -- Can a person correct thinking errors? -- Epilogue